Preparation method of corrosion-resistant coating of TiB2 reinforced Al-based composite material

By preparing a combined coating of anodized aluminum ceramic bottom layer and Al2O3/La2O3/silane coating on the surface of TiB2-strengthening Al-based composite material, the problem of insufficient uniformity and integrity of the anodized film is solved, and the corrosion resistance of the material is significantly improved.

CN119736685AActive Publication Date: 2025-04-01KUNMING UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510020336.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-01
Estimated Expiration
2045-01-07

AI Technical Summary

Technical Problem

The uniformity and integrity of the anodic oxide film of TiB2-reinforced Al-based composite material is insufficient, resulting in low corrosion resistance.

Method used

The combined coating of anodized aluminum ceramic bottom layer and Al2O3/La2O3/silane coating film was used to synthesize the Al2O3/La2O3/silane coating by hydrothermal co-precipitation method to seal the pores of the anodized film and form a thin film to improve corrosion resistance.

Benefits of technology

The corrosion resistance of TiB2-enhanced Al-based composite materials is significantly improved, the corrosion current density is reduced, and the barrier ability and stability of the coating are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to a preparation method of a corrosion-resistant coating of a TiB2 reinforced Al-based composite material, and belongs to the technical field of metal surface treatment. The invention discloses a corrosion-resistant coating of a TiB2 reinforced Al-based composite material. The corrosion-resistant coating comprises an anodic aluminum oxide ceramic bottom layer and an Al2O3 / La2O3 / silane coating film which are prepared on the surface of the TiB2 reinforced Al-based composite material, anodized aluminum is used as a bottom layer, so that the adhesive force between the coatings can be improved; the Al2O3 / La2O3 / silane coating synthesized by a hydrothermal coprecipitation method can seal pores of an anodic oxide film and form a thin film on the surface of the anodic oxide film, has good corrosion resistance, and can play roles in increasing blocking, sealing the pores and improving the corrosion resistance of the coating. The composite coating can overcome the defect that uniform and compact Al2O3 oxidation films are difficult to form on the surfaces of TiB2 reinforced particles, and the protective coating with good corrosion resistance is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a corrosion-resistant coating of a TiB2-reinforced Al-based composite material, and belongs to the technical field of metal surface treatment. Background Art

[0002] Aluminum alloys have a series of excellent properties such as low density, high strength, and moderate fatigue resistance. They have been widely used in aerospace, rail transportation, national defense, military industry, and shipbuilding industries. Compared with traditional aluminum alloys, aluminum-based composites have introduced reinforcement phases, showing outstanding advantages such as high specific strength / specific stiffness, high elastic modulus, fatigue resistance, and wear resistance. However, the oxide film on the surface of aluminum alloys will be corroded in an environment containing chloride ions, and pitting, intergranular corrosion, and stress corrosion are prone to occur. The latest research shows that ceramic particles can enhance the microstructure and properties of aluminum alloys, among which TiB2 is considered to be one of the ideal reinforcements for aluminum-based composites due to its high melting point, high hardness, and good grain boundary structure. The addition of in-situ TiB2 particles can significantly strengthen aluminum alloys, but there is a potential difference between TiB2 particles and the aluminum matrix. As a cathode, the rapid dissolution of the matrix is ​​promoted to promote the formation of pitting holes, which reduces the corrosion resistance of Al-based composites.

[0003] As the most effective method for corrosion protection of aluminum alloys, surface treatment technology is widely used in the field of corrosion protection of aluminum alloys. There are many methods for surface treatment of aluminum, and the commonly used surface modification methods include electroplating, anodizing, micro-arc oxidation, laser cladding, etc. It depends on the purpose of use in various operating environments. Among the many surface treatment methods, the anodizing process is simple, the oxide film formed is more uniform, and has better mechanical properties. The anodizing process is affected by many factors, including the properties of the electrolyte, the oxidation temperature, the oxidation time, etc. However, according to previous studies on the electrochemical properties of anodized aluminum materials, it is shown that due to the formation of a weak barrier-type oxide film, the applicability of TiB2-reinforced Al-based composite materials to anodizing treatment is low, and simple anodizing treatment cannot significantly improve the corrosion resistance of the alloy surface. At the same time, due to the complexity of the organization of the TiB2-reinforced Al-based composite material, the uniformity and integrity of the oxide film are greatly affected, and the corrosion resistance is further reduced. Therefore, studying effective protection methods to improve the corrosion resistance of in-situ self-generated TiB2-reinforced Al-based composite materials has become an important task in this field. Summary of the invention

[0004] Aiming at the technical problem that the uniformity and integrity of the oxide film prepared by anodization are insufficient due to the complexity of the organization of TiB2-reinforced Al-based composite materials, thus resulting in low corrosion resistance, the present invention proposes a method for preparing a corrosion-resistant coating of a TiB2-reinforced Al-based composite material, and the corrosion-resistant coating of the TiB2-reinforced Al-based composite material includes an anodized aluminum ceramic base layer and an Al2O3 / La2O3 / silane coating film prepared on the surface of the TiB2-reinforced Al-based composite material; using anodized aluminum as the base layer can improve the adhesion between the coatings; the Al2O3 / La2O3 / silane coating synthesized by a hydrothermal coprecipitation method can close the pores of the anodized film and form a thin film on the surface with good corrosion resistance, which can play a role in increasing the barrier, closing the pores, and improving the corrosion resistance of the coating. The composite coating of the present invention can overcome the defect that it is difficult to form a uniform and dense Al2O3 oxide film on the surface of TiB2-reinforced particles, and obtain a protective coating with good corrosion resistance.

[0005] A method for preparing a corrosion-resistant coating of a TiB2-reinforced Al-based composite material, the specific steps are as follows: (1) The TiB2 reinforced Al-based composite material is subjected to surface pretreatment to obtain a surface pretreated TiB2 reinforced Al-based composite material; (2) Using a surface pretreated TiB2 reinforced Al-based composite material as an anode electrode and a lead plate as a cathode electrode, immersing the anode electrode and the cathode electrode in electrolyte A for anodic oxidation, thereby obtaining a porous Al2O3 ceramic coating on the surface of the TiB2 reinforced Al-based composite material; the electrolyte A contains H2SO4, C6H8O7, Al(SO4)3, Ce(SO4)2 and propylene glycol; (3) Dissolve zinc nitrate, aluminum nitrate, lanthanum nitrate and cysteine ​​in deionized water to form a mixed solution, heat the mixed solution to a temperature of 60-95°C and keep it warm for 1-8 hours, and adjust the pH value of the system to 9.5-10.5 with NOH solution to obtain solution B; (4) adding γ-aminopropyltriethoxysilane and lanthanum nitrate to a deionized water-ethanol solution in sequence and stirring to obtain a mixed solution, adjusting the pH value of the mixed solution to 3.5-4.5 with nitric acid and ammonia water, and performing a hydrolysis reaction at a temperature of 25-90° C. for 24-48 hours to obtain a silane solution C; (5) Mix solution B and silane solution C evenly to obtain solution D; (6) The TiB2 reinforced Al-based composite material having a porous Al2O3 ceramic coating on its surface is placed in a sealed solution D, heated to a temperature of 110-150°C and kept warm for 6-12 hours to co-deposit an Al2O3 / La2O3 / silane coating on the surface of the TiB2 reinforced Al-based composite material.

[0006] Preferably, the surface pretreatment method in step (1) is as follows: the surface of the TiB2-reinforced Al-based composite material is polished with sandpaper, then added to a NaOH solution, alkaline-soaked for 5 to 60 seconds at a temperature of 60 to 85°C, then added to a hydrochloric acid-nitric acid mixed acid solution for activation treatment for 1 to 5 minutes, and then washed with deionized water and stored in anhydrous ethanol for later use.

[0007] More preferably, the concentration of the NaOH solution is 0.5-2 mol / L, the concentration of hydrochloric acid in the hydrochloric acid-nitric acid mixed acid solution is 0.5-1.5 mol / L, and the concentration of nitric acid is 3-6 mol / L.

[0008] Preferably, in the electrolyte A of step (2), H2SO4 150-200 g / L, C6H8O7 10-20 g / L, Al(SO4)3 1-8 g / L, Ce(SO4)2 1-10 g / L, propylene glycol 5-15 g / L, and the solvent is deionized water.

[0009] More preferably, the inter-electrode distance between the anode electrode and the cathode electrode is 5-10 nm, the forward constant voltage of the anodic oxidation is 10-60 V, and the anodic oxidation time is 10-60 min.

[0010] Preferably, in the mixed solution of step (3), zinc nitrate comprises 8-15 g / L, aluminum nitrate comprises 1-10 g / L, lanthanum nitrate comprises 0.5-2 g / L, and cysteine ​​comprises 1-10 g / L.

[0011] Preferably, the mixed solution in step (4) contains 50-150 ml / L of γ-aminopropyltriethoxysilane and 1-4 g / L of lanthanum nitrate.

[0012] Preferably, in step (5), the volume of the silane solution C accounts for 5-40% of the volume of the solution B.

[0013] The beneficial effects of the present invention are: (1) The present invention uses sulfuric acid (H2SO4), citric acid (C6H8O7), aluminum sulfate (Al(S04)3), cerium sulfate tetrahydrate (Ce(SO4)2·4H2O), and propylene glycol (C3H8O3) as a composite acid electrolyte to improve the performance of the TiB2-reinforced Al-based composite material anodized film; improve the generation efficiency of the oxide film, reduce the holes and defects on the surface of the oxide film, and increase the density of the oxide film; (2) The present invention adds an organic additive, propylene glycol, to change the chemical or electrochemical behavior of the TiB2-reinforced Al-based composite material during the anodization process, reduce the dissolution rate and porosity of the film, and add an inorganic additive, rare earth salt (Ce(SO4)2·4H2O), to increase the thickness of the barrier layer; (3) The present invention utilizes the property of silane coupling agent to react with functional groups on the surface of metal and its oxide to improve the dispersibility and stability of its components in the matrix, and prepares Al2O3 / La2O3 / silane coating on the anodic oxide film by hydrothermal co-deposition method, wherein Al2O3 / La2O3 seals the pores of the anodic oxide film and the density of the oxide film, and at the same time, a layer of Al2O3 / La2O3 / silane coating formed on the surface of the anodic oxide film can prevent it from contacting with the corrosive solution, thereby enhancing the corrosion resistance; (4) The corrosion-resistant coating of the TiB2-reinforced Al-based composite material of the present invention was subjected to electrochemical testing in a 3.5% NaCl solution. The corrosion current of the coating was two orders of magnitude lower than that of the TiB2-reinforced Al-based composite material without surface treatment and about 100 times lower than that of the anodized TiB2-reinforced Al-based composite material. The corrosion resistance is very significant. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 The potentiodynamic polarization curve of the anodic oxidation + Al2O3 / La2O3 / silane coating prepared on the surface of the TiB2-reinforced Al-based composite material in Example 1; Figure 2 The potentiodynamic polarization curves of the TiB2 reinforced Al-based composite materials with different surface treatments in Example 2; Figure 3 EIS results of TiB2 reinforced Al-based composites with different surface treatments in Example 2; Figure 4 The SEM morphology and EDS composition diagram of the Al2O3 / La2O3 / silane coating prepared on the surface of the TiB2 reinforced Al-based composite material in Example 2; Figure 5 The potentiodynamic polarization curve of the anodic oxidation + Al2O3 / La2O3 / silane coating prepared on the surface of the TiB2-reinforced Al-based composite material in Example 3; Figure 6 This is the potentiodynamic polarization curve of the anodic oxidation + Al2O3 / La2O3 / silane coating prepared on the surface of the TiB2 reinforced Al-based composite material in Example 4. DETAILED DESCRIPTION

[0015] The present invention is further described in detail below in conjunction with specific implementation modes, but the protection scope of the present invention is not limited to the described contents.

[0016] Embodiment 1: A method for preparing a corrosion-resistant coating of a TiB2-reinforced Al-based composite material, the specific steps are as follows: (1) The TiB2 reinforced Al-based composite material is subjected to surface pretreatment to obtain a surface pretreated TiB2 reinforced Al-based composite material; the surface pretreatment method is as follows: the surface of the TiB2 reinforced Al-based composite material is polished with sandpaper, then added to a NaOH solution with a concentration of 1 mol / L, alkaline soaked for 5 seconds at a temperature of 60°C, then added to a hydrochloric acid-nitric acid mixed acid solution (the hydrochloric acid concentration in the hydrochloric acid-nitric acid mixed acid solution is 0.5 mol / L, and the nitric acid concentration is 3 mol / L) for activation treatment for 1 minute, and then washed with deionized water and stored in anhydrous ethanol for later use; (2) Using the surface pretreated TiB2 reinforced Al-based composite material as the anode electrode and the lead plate as the cathode electrode, immersing the anode electrode and the cathode electrode in electrolyte A (the inter-electrode distance between the anode electrode and the cathode electrode is 5 nm), and performing anodization for 10 min at a forward constant voltage of 10 V to obtain a porous Al2O3 ceramic coating on the surface of the TiB2 reinforced Al-based composite material; the electrolyte A contains 160 g / L sulfuric acid H2SO4, 10 g / L citric acid C6H8O7, 1 g / L aluminum sulfate Al(SO4)3, 1 g / L cerium sulfate Ce(SO4)2, and 5 g / L glycerol, and the solvent is deionized water; (3) Dissolve zinc nitrate Zn(NO3)2, aluminum nitrate Al(NO3)3, lanthanum nitrate La(NO3)3, and cysteine ​​(Cys) in deionized water to form a mixed solution, heat the mixed solution to 60°C and keep it warm for 3 hours, adjust the pH value of the system to 10.5 with NOH solution, and obtain solution B; the mixed solution contains 28 g / L zinc nitrate Zn(NO3), 31 g / L aluminum nitrate Al(NO3), 31 g / L lanthanum nitrate La(NO3), and 1 g / L cysteine ​​(Cys); (4) Adding γ-aminopropyltriethoxysilane and lanthanum nitrate to a deionized water-ethanol solution (the volume ratio of deionized water to ethanol is 1:1) in sequence, stirring and mixing to obtain a mixed solution, adjusting the pH value of the mixed solution to 4.5 with nitric acid and ammonia water, and performing a hydrolysis reaction at a temperature of 35° C. for 24 hours to obtain a silane solution C; the mixed solution contains 60 ml / L of γ-aminopropyltriethoxysilane and 1 g / L of lanthanum nitrate; (5) Mixing solution B and silane solution C to obtain solution D; the silane solution C accounts for 5% of the volume of solution B; (6) The TiB2 reinforced Al-based composite material having a porous Al2O3 ceramic coating on the surface is placed in a sealed solution D, heated to 110°C and kept warm for 6 hours to co-deposit an Al2O3 / La2O3 / silane coating on the surface of the TiB2 reinforced Al-based composite material; The polarization curve of the sample was detected at room temperature using a three-electrode system. The sample was used as the working electrode, the saturated calomel electrode was used as the reference electrode, the platinum sheet was used as the counter electrode, and the 3.5wt.% NaCl solution was used as the electrolyte. The voltage scanning range was set to OCP±0.25V, and the scanning rate was 2mV / s. The potentiodynamic polarization curve of the anodic oxidation + Al2O3 / La2O3 / silane coating prepared on the surface of the TiB2-reinforced Al-based composite material in Example 1 is shown in FIG. Figure 1 ,from Figure 1 It can be seen that the polarization curve represents the relationship between electrode potential and polarization current density, revealing the basic law of metal corrosion. The corrosion difficulty of the material is evaluated by the self-corrosion potential and self-corrosion current density. The self-corrosion current indicates the speed of corrosion. The lower the self-corrosion current, the better the corrosion resistance. Compared with the original sample without surface treatment, the polarization curve of the surface treated sample in Example 1 moves downward, indicating that the anodized + Al2O3 / La2O3 / silane coating generated after surface treatment reduces the self-corrosion current density of the composite material and improves the corrosion resistance; The Ecor and icorr data of the TiB2 reinforced Al-based composite material in this embodiment are shown in Table 1. Table 1 Ecor and icorr data of TiB2 reinforced Al-based composite materials after surface treatment in this embodiment Corrosion voltage(V) Corrosion current density (μA·cm~2) No surface treatment ~0.799 24.93 Anodic oxidation + Al2O3 / La2O3 / Silane coating ~0.763 0.7336 From Table 1, it can be seen that the corrosion potentials of the anodic oxidation + Al2O3 / La2O3 / silane coating obtained by surface treatment in this embodiment are ~0.799V and ~0.763V respectively; the corrosion voltages of the samples are not much different, but their corrosion currents are quite different. The corrosion current density of the untreated surface is 24.93μA·cm ~2 ; The corrosion current density of the anodic oxidation + Al2O3 / La2O3 / silane coating is 0.7336μA·cm ~2 , which is about 30 times lower than the original sample. According to Faraday's law, the electrochemical corrosion rate increases linearly with the corrosion current density. The smaller the corrosion current density, the slower the corrosion rate of the alloy and the better the corrosion resistance. This shows that anodization + Al2O3 / La2O3 / silane coating improves the corrosion resistance of TiB2-reinforced Al-based composites. Figure 1 The polarization curve results correspond to .

[0017] Embodiment 2: A method for preparing a corrosion-resistant coating of a TiB2-reinforced Al-based composite material, the specific steps are as follows: (1) The TiB2 reinforced Al-based composite material is subjected to surface pretreatment to obtain a surface pretreated TiB2 reinforced Al-based composite material; the surface pretreatment method is as follows: the surface of the TiB2 reinforced Al-based composite material is polished with sandpaper, then added to a NaOH solution with a concentration of 1.25 mol / L, alkaline soaked for 20 seconds at a temperature of 70°C, then added to a hydrochloric acid-nitric acid mixed acid solution (the hydrochloric acid concentration in the hydrochloric acid-nitric acid mixed acid solution is 1 mol / L, and the nitric acid concentration is 4.5 mol / L) for activation treatment for 2 minutes, and then washed with deionized water and stored in anhydrous ethanol for later use; (2) Using the surface pretreated TiB2 reinforced Al-based composite material as the anode electrode and the lead plate as the cathode electrode, immersing the anode electrode and the cathode electrode in electrolyte A (the inter-electrode distance between the anode electrode and the cathode electrode is 8 nm), and performing anodization for 30 min at a forward constant voltage of 15 V to obtain a porous Al2O3 ceramic coating on the surface of the TiB2 reinforced Al-based composite material; the electrolyte A contains 180 g / L sulfuric acid H2SO4, 15 g / L citric acid C6H8O7, 35 g / L aluminum sulfate Al(SO4), 25 g / L cerium sulfate Ce(SO4), 9 g / L glycerol, and the solvent is deionized water; (3) Dissolve zinc nitrate Zn(NO3)2, aluminum nitrate Al(NO3)3, lanthanum nitrate La(NO3)3, and cysteine ​​(Cys) in deionized water to form a mixed solution, heat the mixed solution to 70°C and keep it warm for 6 hours, adjust the pH value of the system to 10 with NOH solution, and obtain solution B; the mixed solution contains 12 g / L zinc nitrate Zn(NO3)2, 36 g / L aluminum nitrate Al(NO3), 31.78 g / L lanthanum nitrate La(NO3), and 2.5 g / L cysteine ​​(Cys); (4) γ-aminopropyltriethoxysilane and lanthanum nitrate were added to a deionized water-ethanol solution (the volume ratio of deionized water to ethanol was 1:1) in sequence, and the mixture was stirred to obtain a mixed solution. The pH value of the mixed solution was adjusted to 4 with nitric acid and ammonia water, and the mixture was hydrolyzed at 25° C. for 24 h to obtain a silane solution C; the mixed solution contained 100 ml / L of γ-aminopropyltriethoxysilane and 2 g / L of lanthanum nitrate; (5) Mixing solution B and silane solution C to obtain solution D; the silane solution C accounts for 10% of the volume of solution B; (6) The TiB2 reinforced Al-based composite material having a porous Al2O3 ceramic coating on the surface is placed in a sealed solution D, heated to 120°C and kept warm for 9 hours to co-deposit an Al2O3 / La2O3 / silane coating on the surface of the TiB2 reinforced Al-based composite material; The coating was electrochemically tested using a CHI760e electrochemical workstation: a typical three-electrode system was used, with the sample, platinum electrode and saturated calomel electrode (SCE) used as the working electrode, auxiliary electrode and reference electrode respectively; the corrosion electrolyte was a 3.5% NaCl aqueous solution, the voltage scanning range was set to OCP±0.25V, and the scanning rate was 1mV / s; the polarization curve and impedance spectrum obtained by the electrochemical test were used to reflect the corrosion resistance of the coating; The potentiodynamic polarization curves of TiB2 reinforced Al-based composite materials with different surface treatments in this embodiment are shown in Figure 2 ;from Figure 2 It can be seen that compared with the original sample without surface treatment, the polarization curve of the anodized + Al2O3 / La2O3 / silane coating has moved downward as a whole, and the movement amplitude is large, indicating that the anodized + Al2O3 / La2O3 / silane coating generated after surface treatment significantly reduces the self-corrosion current density of the composite material, and the corrosion resistance is greatly improved. At the same time, it can be seen that the polarization curve of the anodized + Al2O3 / La2O3 / silane coating has an obvious corrosion current density platform between ~0.8V and ~0.7V, indicating that it has a good passivation phenomenon, and the better the corrosion resistance; The Ecor and icorr data of the TiB2 reinforced Al-based composite materials with different surface treatments in this embodiment are shown in Table 2. Table 2 Ecor and icorr data of TiB2 reinforced Al-based composites with different surface treatments Corrosion voltage(V) Corrosion current density (μA·cm~2) No surface treatment ~0.799 24.93 Anodizing only ~0.747 3.413 Anodic oxidation + Al2O3 / La2O3 / Silane coating ~0.830 0.01054 From Table 2, we can see that the corrosion potentials of the untreated, anodized and anodized + Al2O3 / La2O3 / silane coatings are ~0.799V, ~0.747V and ~0.830V respectively. The corrosion voltages of the three samples are not much different, but their corrosion currents are quite different. The corrosion current density of the untreated samples is 24.93μA·cm ~2 ; The corrosion current density of anodic oxidation alone is 3.413 μA·cm ~2 , which is 8 times lower than that of the original sample; the corrosion current density of the anodized + Al2O3 / La2O3 / silane coating is 0.01054μA·cm ~2 , which is about 240 times lower than the original sample and about 30 times lower than the sample only anodized. According to Faraday's law, the electrochemical corrosion rate increases linearly with the corrosion current density. The smaller the corrosion current density, the slower the corrosion rate of the alloy and the better the corrosion resistance. This shows that the anodized + Al2O3 / La2O3 / silane coating prepared in Example 2 greatly improves the corrosion resistance of the TiB2-reinforced Al-based composite material. The EIS results of TiB2 reinforced Al-based composites with different surface treatments in this example are shown in Figure 3 , where (a) Nyquist diagram; (b) Bode diagram, from Figure 3 It can be seen that the capacitive reactance arcs of the three samples gradually increase in the order of no surface treatment < only anodization < anodization + Al2O3 / La2O3 / silane coating. Generally, the larger the radius of the capacitive arc of the Nyquist diagram, the better the corrosion resistance. The capacitive reactance arc radius of the anodized + Al2O3 / La2O3 / silane coating sample is the largest, the oxide film is the thickest, and the corrosion resistance is the best. The Bode diagram shows the impedance modulus |Z| of the sample. The impedance modulus |Z| at low frequency is used to qualitatively judge the corrosion resistance of the surface oxide film. The larger the impedance modulus, the thicker the oxide film, and the better the corrosion resistance. The impedance modulus |Z| measured by anodized + Al2O3 / La2O3 / silane coating is the largest, and the corrosion resistance is good; Combining the results of the Nyquist diagram and the Bode diagram, it can be seen that the anodized + Al2O3 / La2O3 / silane coating of this embodiment has good corrosion resistance; The SEM morphology and EDS composition diagram of the Al2O3 / La2O3 / silane coating prepared on the surface of the TiB2 reinforced Al-based composite material in this embodiment are shown in Figure 4 ,from Figure 4 It can be seen that the surface of the anodized + Al2O3 / La2O3 / silane coating sample is mainly composed of Al, O, La, Ti, Si, and C elements. The distribution of Al, O, and La elements is highly overlapped, indicating that Al2O3 and La2O3 are generated; at the same time, there are also aggregations of Al, O, and La elements in the area where Ti elements are gathered, indicating that Al2O3 and La2O3 also exist on the ceramic particles TiB2, that is, Al2O3 and La2O3 are distributed on the entire surface of the sample. At the same time, the presence of Si and C elements indicates the presence of silane.

[0018] Embodiment 3: A method for preparing a corrosion-resistant coating of a TiB2-reinforced Al-based composite material, the specific steps are as follows: (1) The TiB2 reinforced Al-based composite material is subjected to surface pretreatment to obtain a surface pretreated TiB2 reinforced Al-based composite material; the surface pretreatment method is as follows: the surface of the TiB2 reinforced Al-based composite material is polished with sandpaper, then added to a NaOH solution with a concentration of 2 mol / L, alkaline soaked for 60 seconds at a temperature of 85°C, then added to a hydrochloric acid-nitric acid mixed acid solution (the hydrochloric acid concentration in the hydrochloric acid-nitric acid mixed acid solution is 1 mol / L, and the nitric acid concentration is 5 mol / L) for activation treatment for 5 minutes, and then washed with deionized water and stored in anhydrous ethanol for later use; (2) Using a surface pretreated TiB2 reinforced Al-based composite material as an anode electrode and a lead plate as a cathode electrode, immersing the anode electrode and the cathode electrode in electrolyte A (the inter-electrode distance between the anode electrode and the cathode electrode is 10 nm), and performing anodization for 15 minutes at a forward constant voltage of 60 V to obtain a porous Al2O3 ceramic coating on the surface of the TiB2 reinforced Al-based composite material; the electrolyte A contains 200 g / L sulfuric acid H2SO4, 20 g / L citric acid C6H8O7, 38 g / L aluminum sulfate Al(SO4), 10 g / L cerium sulfate Ce(SO4), and 15 g / L glycerol, and the solvent is deionized water; (3) Dissolve zinc nitrate Zn(NO3)2, aluminum nitrate Al(NO3)3, lanthanum nitrate La(NO3)3, and cysteine ​​(Cys) in deionized water to form a mixed solution, heat the mixed solution to 95°C and keep it warm for 8 hours, adjust the pH value of the system to 9.5 with NOH solution, and obtain solution B; the mixed solution contains 15 g / L zinc nitrate Zn(NO3)2, 10 g / L aluminum nitrate Al(NO3)3, 32 g / L lanthanum nitrate La(NO3), and 10 g / L cysteine ​​(Cys); (4) γ-aminopropyltriethoxysilane and lanthanum nitrate were added to a deionized water-ethanol solution (the volume ratio of deionized water to ethanol was 1:1) in sequence, and the mixture was stirred to obtain a mixed solution. The pH value of the mixed solution was adjusted to 3.5 with nitric acid and ammonia water, and the mixture was hydrolyzed at 80° C. for 36 h to obtain a silane solution C; the mixed solution contained 150 ml / L of γ-aminopropyltriethoxysilane and 4 g / L of lanthanum nitrate; (5) Mixing solution B and silane solution C evenly to obtain solution D; the silane solution C accounts for 35% of the volume of solution B; (6) The TiB2 reinforced Al-based composite material having a porous Al2O3 ceramic coating on the surface is placed in a sealed solution D, heated to 150°C and kept warm for 12 hours to co-deposit an Al2O3 / La2O3 / silane coating on the surface of the TiB2 reinforced Al-based composite material; (7) A three-electrode system was used to detect the polarization curve of the sample at room temperature. The sample to be tested was used as the working electrode, the saturated calomel electrode was used as the reference electrode, the platinum sheet was used as the counter electrode, and a 3.5 wt.% NaCl solution was used as the electrolyte. The voltage scanning range was set to OCP ± 0.25 V, and the scanning rate was 2 mV / s.

[0019] The potentiodynamic polarization curve of the anodic oxidation + Al2O3 / La2O3 / silane coating prepared on the surface of the TiB2-reinforced Al-based composite material in Example 3 is shown in FIG. Figure 5 .from Figure 5It can be seen that compared with the original sample without surface treatment, the polarization curve of the sample after surface treatment in Example 3 shifts downward, indicating that the anodic oxidation + Al2O3 / La2O3 / silane coating generated after surface treatment reduces the self-corrosion current density of the composite material and improves the corrosion resistance; The Ecor and icorr data of the TiB2 reinforced Al-based composite material in this embodiment are shown in Table 3. Table 3 Ecor and icorr data of TiB2 reinforced Al-based composites after surface treatment in Example 3 Corrosion voltage(V) Corrosion current density (μA·cm~2) No surface treatment ~0.799 24.93 Anodic oxidation + Al2O3 / La2O3 / Silane coating ~0.749 1.216 From Table 1, it can be seen that the corrosion potentials of the anodic oxidation + Al2O3 / La2O3 / silane coating obtained without surface treatment and with surface treatment in Example 1 are ~0.799V and ~0.763V respectively; the corrosion voltages of the three samples are not much different, but their corrosion currents are quite different. The corrosion current density of the untreated sample is 24.93μA·cm ~2 ; The corrosion current density of the anodic oxidation + Al2O3 / La2O3 / silane coating is 0.7336μA·cm ~2 , which is about 30 times lower than the original sample. According to Faraday's law, the electrochemical corrosion rate increases linearly with the corrosion current density. The smaller the corrosion current density, the slower the corrosion rate of the alloy and the better the corrosion resistance. This shows that anodization + Al2O3 / La2O3 / silane coating improves the corrosion resistance of TiB2-reinforced Al-based composites. Figure 5 The polarization curve results correspond to .

[0020] Embodiment 4: A method for preparing a corrosion-resistant coating of a TiB2-reinforced Al-based composite material, the specific steps are as follows: (1) The TiB2 reinforced Al-based composite material is subjected to surface pretreatment to obtain a surface pretreated TiB2 reinforced Al-based composite material; the surface pretreatment method is as follows: the surface of the TiB2 reinforced Al-based composite material is polished with sandpaper, then added to a NaOH solution with a concentration of 1.5, alkaline soaked for 30 seconds at a temperature of 75°C, then added to a hydrochloric acid-nitric acid mixed acid solution (the hydrochloric acid concentration in the hydrochloric acid-nitric acid mixed acid solution is 1 mol / L, and the nitric acid concentration is 5 mol / L) for activation treatment for 3 minutes, and then washed with deionized water and stored in anhydrous ethanol for later use; (2) Using a surface pretreated TiB2 reinforced Al-based composite material as an anode electrode and a lead plate as a cathode electrode, immersing the anode electrode and the cathode electrode in electrolyte A (the inter-electrode distance between the anode electrode and the cathode electrode is 20 nm), and performing anodization for 20 min at a forward constant voltage of 20 V to obtain a porous Al2O3 ceramic coating on the surface of the TiB2 reinforced Al-based composite material; the electrolyte A contains 188 g / L H2SO4, 18 g / L C6H8O7, 35.5 g / L Al(SO4), 3 g / L Ce(SO4), and 10 g / L glycerol, and the solvent is deionized water; (3) Dissolve zinc nitrate Zn(NO3)2, aluminum nitrate Al(NO3)3, lanthanum nitrate La(NO3)3, and cysteine ​​(Cys) in deionized water to form a mixed solution, heat the mixed solution to 80°C and keep it warm for 6 hours, adjust the pH value of the system to 10 with NOH solution, and obtain solution B; the mixed solution contains 10 g / L zinc nitrate Zn(NO3), 38.8 g / L aluminum nitrate Al(NO3), 31.1 g / L lanthanum nitrate La(NO3), and 5 g / L cysteine ​​(Cys); (4) γ-aminopropyltriethoxysilane and lanthanum nitrate were sequentially added to a deionized water-ethanol solution (the volume ratio of deionized water to ethanol was 1:1), stirred and mixed to obtain a mixed solution, nitric acid and ammonia water were used to adjust the pH value of the mixed solution to 4.5, and hydrolyzed at 50° C. for 12 h to obtain a silane solution C; the mixed solution contained 100 ml / L of γ-aminopropyltriethoxysilane and 1.9 g / L of lanthanum nitrate; (5) Mixing solution B and silane solution C to obtain solution D; the silane solution C accounts for 15% of the volume of solution B; (6) The TiB2 reinforced Al-based composite material having a porous Al2O3 ceramic coating on the surface is placed in a sealed solution D, heated to 120°C and kept warm for 6 hours to co-deposit an Al2O3 / La2O3 / silane coating on the surface of the TiB2 reinforced Al-based composite material; The polarization curve of the sample was detected at room temperature using a three-electrode system. The sample was used as the working electrode, the saturated calomel electrode was used as the reference electrode, the platinum sheet was used as the counter electrode, and the 3.5wt.% NaCl solution was used as the electrolyte. The voltage scanning range was set to OCP±0.25V, and the scanning rate was 2mV / s. The potentiodynamic polarization curve of the anodic oxidation + Al2O3 / La2O3 / silane coating prepared on the surface of the TiB2-reinforced Al-based composite material in Example 4 is shown in FIG. Figure 6 ;from Figure 6It can be seen that compared with the original sample without surface treatment, the polarization curve of the sample after surface treatment in Example 4 shifts downward, indicating that the anodic oxidation + Al2O3 / La2O3 / silane coating generated after surface treatment reduces the self-corrosion current density of the composite material and improves the corrosion resistance; The Ecor and icorr data of the TiB2 reinforced Al-based composite material in this embodiment are shown in Table 4. Table 4 Ecor and icorr data of TiB2 reinforced Al-based composites after surface treatment in Example 4 Corrosion voltage(V) Corrosion current density (μA·cm~2) No surface treatment ~0.799 24.93 Anodic oxidation + Al2O3 / La2O3 / Silane coating ~0.790 0.3118 As can be seen from Table 4, the corrosion potentials of the anodic oxidation + Al2O3 / La2O3 / silane coating obtained without surface treatment and with surface treatment in Example 4 are ~0.799V and ~0.790V, respectively. The corrosion voltages of the samples are not much different, but their corrosion currents are quite different. The corrosion current density of the untreated sample is 24.93μA·cm ~2 ; The corrosion current density of the anodic oxidation + Al2O3 / La2O3 / silane coating is 0.3118μA·cm ~2 , which is about 80 times lower than the original sample. According to Faraday's law, the electrochemical corrosion rate increases linearly with the corrosion current density. The smaller the corrosion current density, the slower the corrosion rate of the alloy and the better the corrosion resistance. This shows that anodization + Al2O3 / La2O3 / silane coating improves the corrosion resistance of TiB2-reinforced Al-based composites. Figure 6 The polarization curve results correspond to .

[0021] The specific implementation modes of the present invention are described in detail above, but the present invention is not limited to the above implementation modes, and various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.

Claims

1. A method for preparing a corrosion-resistant coating of a TiB2-reinforced Al-based composite material, characterized in that: The specific steps are as follows: (1) The TiB2 reinforced Al-based composite material is subjected to surface pretreatment to obtain a surface pretreated TiB2 reinforced Al-based composite material; (2) Using a surface pretreated TiB2 reinforced Al-based composite material as an anode electrode and a lead plate as a cathode electrode, immersing the anode electrode and the cathode electrode in electrolyte A for anodic oxidation, thereby obtaining a porous Al2O3 ceramic coating on the surface of the TiB2 reinforced Al-based composite material; the electrolyte A contains H2SO4, C6H8O7, Al(SO4)3, Ce(SO4)2 and propylene glycol; (3) Dissolve zinc nitrate, aluminum nitrate, lanthanum nitrate and cysteine ​​in deionized water to form a mixed solution, heat the mixed solution to a temperature of 60-95°C and keep it warm for 1-8 hours, and adjust the pH value of the system to 9.5-10.5 with NOH solution to obtain solution B; (4) adding γ-aminopropyltriethoxysilane and lanthanum nitrate to a deionized water-ethanol solution in sequence and stirring to obtain a mixed solution, adjusting the pH value of the mixed solution to 3.5-4.5 with nitric acid and ammonia water, and performing a hydrolysis reaction at a temperature of 25-90° C. for 24-48 hours to obtain a silane solution C; (5) Mix solution B and silane solution C evenly to obtain solution D; (6) The TiB2 reinforced Al-based composite material having a porous Al2O3 ceramic coating on its surface is placed in a sealed solution D, heated to a temperature of 110-150°C and kept warm for 6-12 hours to co-deposit an Al2O3 / La2O3 / silane coating on the surface of the TiB2 reinforced Al-based composite material.

2. The method for preparing the corrosion-resistant coating of the TiB2-reinforced Al-based composite material according to claim 1, characterized in that: The surface pretreatment method of step (1) is as follows: the surface of the TiB2 reinforced Al-based composite material is polished with sandpaper, then added to a NaOH solution, alkaline-soaked for 5 to 60 seconds at a temperature of 60 to 85°C, then added to a hydrochloric acid-nitric acid mixed acid solution for activation treatment for 1 to 5 minutes, and then washed with deionized water and stored in anhydrous ethanol for later use.

3. The method for preparing the corrosion-resistant coating of the TiB2-reinforced Al-based composite material according to claim 2, characterized in that: The concentration of NaOH solution is 0.5~2mol / L, the concentration of hydrochloric acid in the hydrochloric acid-nitric acid mixed acid solution is 0.5~1.5mol / L, and the concentration of nitric acid is 3~6mol / L.

4. The method for preparing the corrosion-resistant coating of the TiB2-reinforced Al-based composite material according to claim 1, characterized in that: Step (2) The electrolyte A contains 150-200 g / L H2SO4, 10-20 g / L C6H8O7, 1-8 g / L Al(SO4)3, 1-10 g / L Ce(SO4)2, and 5-15 g / L propylene glycol, and the solvent is deionized water.

5. The method for preparing the corrosion-resistant coating of the TiB2-reinforced Al-based composite material according to claim 4, characterized in that: The inter-electrode distance between the anode electrode and the cathode electrode is 5-10 nm, the forward constant voltage of the anodic oxidation is 10-60 V, and the anodic oxidation time is 10-60 min.

6. The method for preparing the corrosion-resistant coating of the TiB2-reinforced Al-based composite material according to claim 1, characterized in that: In step (3), the mixed solution contains 8-15 g / L zinc nitrate, 1-10 g / L aluminum nitrate, 0.5-2 g / L lanthanum nitrate, and 1-10 g / L cysteine.

7. The method for preparing the corrosion-resistant coating of the TiB2-reinforced Al-based composite material according to claim 1, characterized in that: In step (4), the mixed solution contains 50-150 ml / L of γ-aminopropyltriethoxysilane and 1-4 g / L of lanthanum nitrate.

8. The method for preparing the corrosion-resistant coating of the TiB2-reinforced Al-based composite material according to claim 1, characterized in that: Step (5) Silane solution C accounts for 5-40% of the volume of solution B.

Citation Information

Patent Citations

  • Two-step electrochemical method for preparing aluminum base composite material surface protection coating

    CN101008098A

  • Preparation method of silane-cerium oxide-hydrotalcite composite coating on surface of magnesium / magnesium alloy matrix

    CN107059005A

  • Preparation method of rare earth element added sulfuric acid-oxalic acid anodic oxidation aluminum film

    CN108517550A

  • Preparing process of anticorrosive coating on surface of aluminium base composite material

    CN1986887A